Analisis Sikap Ilmiah Peserta Didik Melalui Pengalaman Kegiatan Praktikum Pembelajaran Kimia - Nur Inayah Amaliyah; Nurfina Aznam; Shofrina Surya Dewi (Postgraduate, University of Mataram, 2024)
This research aims to analyze and determine the profile of scientific attitudes of class XI students at SMA Negeri 1 Woja, West Nusa Tenggara based on chemistry practicum experience. This research is aquantitative descriptive research with the method used is the survey method. The research instrument used was a closed questionnaire, then analyzed quantitatively by calculating the percentage of the overall score or average value and categorized. The results of the research show that the scientific attitude in the aspect of curiosity got a score of 87.55% with very good criteria, honesty attitude got a score of 83% with good criteria, Objectify attitude got a score of 85.85% with very good criteria, perseverance got a score of 85.96% with very good criteria, conscientiousness got a score of 85.65% with very good criteria, Openness attitude got a score of 87.56% with very good criteria, Being critical thinking got a score of 84.44% with good criteria, responsibility got a score of 87.39% with very good criteria. So it can be concluded that students' scientific attitudes through chemistry practical experience have a score of 75.37% with good criteria.